The Effect of Dividend Policy, Debt Policy and Investment Decisions on Firm’s Value - Mega Octaviany; Sari Puspitarini (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2023)
This research aims to analyze the effect of Dividend Policy, Debt Policy and Investment Decisions on Firm Value. The population in this research are Property and Real Estate sub-sector companies listed on the Indonesia Stock Exchange (BEI) for the period 2014-2020. The sample used in the research was eight companies with the sample selection method of data collection using the documentation method in the form of secondary data obtained from the Indonesia Stock Exchange website and the company annual report. The sample used in the research was 8 (Eight) companies with the sample selection method using purposive sampling. The method of data collection using the documentation method in the form of secondary data on financial statements for the period 2014-2020 obtained from the company website and the Indonesia Stock Exchange website (BEI). The data analysis method uses a Fixed Effect Model with an Ordinary Least Square through the statistical program Eviews 10. The result of this research indicated that Dividend Policy (DPR) has an insignificant negative effect on Firm Value, Debt Policy (DER) has no significant positive effect on Firm Value and Investment Decisions (PER) have an insignificant negative effect on Firm Value